2007
DOI: 10.2166/wst.2007.612
|View full text |Cite
|
Sign up to set email alerts
|

Free ammonia and free nitrous acid inhibition on the anabolic and catabolic processes of Nitrosomonas and Nitrobacter

Abstract: The inhibitory effects of free ammonia (FA) and free nitrous acid (FNA) on the catabolic and anabolic processes of Nitrosomonas and Nitrobacter were investigated using a method that allows decoupling the growth and energy generation processes. Lab-scale sequencing batch reactors (SBRs) were operated for the enrichment of Nitrosomonas and Nitrobacter. Fluorescent In-Situ Hybridization (FISH) analysis showed that the reactors were 82% and 73% enriched with Nitrosomonas and Nitrobacter, respectively. Batch tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(91 citation statements)
references
References 0 publications
4
83
0
3
Order By: Relevance
“…The lack of detection of Nitrospira spp. related NOB during partial nitrification is consistent with previous studies 18,30,31 and was likely due to the propensity of Nitrospira spp. to preferentially grow at lower nitrite concentrations.…”
Section: Article ' Materials and Methodssupporting
confidence: 92%
“…The lack of detection of Nitrospira spp. related NOB during partial nitrification is consistent with previous studies 18,30,31 and was likely due to the propensity of Nitrospira spp. to preferentially grow at lower nitrite concentrations.…”
Section: Article ' Materials and Methodssupporting
confidence: 92%
“…Nitrite accumulation was significantly higher than nitrate at day 1 and the NO 2 − -N/NO x -N ratio increased gradually from 0.2 to 0.7 during the start-up period at day 1. The inhibition of ammonium and nitrite oxidation by free ammonia and nitrous acid is well known Vadivelu et al 2007). The inhibitory effects of substrate concentration, among other factors, such as pH, T, DO and SRT, are strong and complex, due to unionization phenomena.…”
Section: Nitrogen Removal Efficacy In the Absence Of External Carbon mentioning
confidence: 99%
“…Moreover, Bae et al (2001) reported that nitrite accumulation occurred at initial free ammonia concentration of 4.7 mg/L, giving a high NO 2 − /NO X ratio (up to 77 %) in a batch reactor. On the other hand, the works of Vadivelu et al (2007) indicated that nitrite oxidation could be selectively inhibited by free nitrous acid. Nitrite oxidation could be affected more than ammonium oxidation by free ammonia, resulting in accelerating nitrite accumulation in a strong nitrogenous environment.…”
Section: Nitrogen Removal Efficacy In the Absence Of External Carbon mentioning
confidence: 99%
“…These factors included higher free ammonia [4]- [6], hydraulic retention time (HRT) [7], [8], dissolve oxygen (DO) concentration and inhibitor [9]. However, the efficiency of biological nitrogen removal can be improved by maintaining and monitoring the ORP, pH and DO in the nitrification-denitrification process [10].…”
Section: Introductionmentioning
confidence: 99%